Binary open clusters in the Milky Way: photometric and spectroscopic analysis of NGC 5617 and Trumpler 22 - De Silva, G. M. (2015)
Using photometry and high resolution spectroscopy we investigate for the first time the physical connection between the open clusters NGC 5617 and Trumpler 22. Based on new CCD photometry we report their spatial proximity and common age of ~70 Myr. Based on high resolution spectra collected using the HERMES and UCLES spectrographs on the Anglo-Australian telescope, we present radial velocities and abundances for Fe, Na, Mg, Al, Si, Ca and Ni. The measured radial velocities are -38.63 ± 2.25 km s⁻¹ for NGC 5617 and -38.46 ± 2.08 km s⁻¹ for Trumpler 22. The mean metallicity of NGC 5617 was found to be [Fe/H] = -0.18 ± 0.02 and for Trumpler 22 was found to be [Fe/H] = -0.17 ± 0.04. The two clusters share similar abundances across the other elements, indicative of a common chemical enrichment history of these clusters. Together with common motions and ages we confirm that NGC 5617 and Trumpler 22 are a primordial binary cluster pair in the Milky Way.